BCR::ABL1-negative myeloproliferative neoplasms in the era of next-generation sequencing - Mroczkowska-Bękarciak, Aleksandra; Wróbel, Tomasz (Frontiers in Genetics, 2023)
The classical BCR::ABL1-negative myeloproliferative neoplasm such as polycythemia vera (PV), essential thrombocythemia (ET) and myelofibrosis (MF) are clonal diseases with present of characteristic "driver mutations" in one of the genes: JAK2, CALR or MPL. The search for mutations in these 3 genes is required for the diagnosis of MPN. Nevertheless, the progress that has been made in the field of molecular genetics has opened a new era in medicine. The search for additional mutations in MPN is helpful in assessing the risk stratification, disease progresion, transformation to acute myeloid leukemia (AML) or choosing the right treatment. In some cases, advanced technologies are needed to find a clonal marker of the disease and establish a diagnosis. This review focuses on how the use of new technologies like Next Generation Sequencing (NGS) helps in the diagnostics of BCR::ABL1-negative neoplasms.